PENGARUH PERENCANAAN ANGGARAN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP PENYERAPAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI PEMODERASI - Muhammad Iqbal (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2022)
This explanatory research aims to test the hypothesis developed from the budget planning variable and human resource competence on budget absorption, either directly or through the organizational commitment variable as moderator. The research was conducted at the Polewali Mandar Regency Government with a sample of 96/100 respondents. Data were collected through a survey method by distributing questionnaires to each respondent and using multiple regression and moderated regression analysis as data analysis tools. The results showed that budget planning and human resource competence had a positive effect on the absorption rate of the budget. Organizational commitment does not moderate the relationship between budget planning and budget absorption, but is able to moderate the relationship between human resource competence and budget absorption.